KONTRIBUSI OBJEK WISATA TERHADAP PENDAPATAN ASLI DAERAH DI KABUPATEN LIMA PULUH KOTA - Anita Ratu Sitrah; Yurni Suasti (DEPARTEMEN GEOGRAFI FIS UNP, 2021)
The objectives of this study are (1) to describe the amount of contribution of tourism objects to PAD (2) to determine the level of achievement of the contribution of each tourist attraction and the level of tourist visits at each tourist attraction in Lima Puluh Kota Regency during the period 2015-2019. This type of research is secondary data analysis. Data collection techniques are observation, interviews, and documentation. The results of this study are (1) The size of the contribution of tourism objects to the PAD of Lima Puluh Kota Regency from five years from 2015-2019 has fluctuated. For five years, the biggest contribution to PAD was the Harau Valley tourist attraction amounting to Rp. 2,511,825,000 and the lowest was the Banda Taram boat tourism object of Rp. 20,655,000 (2) Within five years of receipt of the contribution amounting to Rp. 6,825,469,000 with the overall average percentage obtained of 59.86%. Within five years of the year, the number of visits to the three tourist objects at most was to the Harau Valley tourist attraction as many as 834,105 people and the few were to the Kapalo Banda Taram tourist attraction with 41,211 people. Based on interviews with tourists, traders, local communities, managers, and tourism experts, the result is that with the presence of tourist objects that contribute to the area, the surrounding community can also work and improve the area. The researcher decided that several supporting facilities needed to be added, such as children's games, photo spots, information banners.